PRACTICE OF STEREOTYPES IN THE TEXT: EXAMPLE OF TRAVEL NARRATIVE - Aktulum, Kubilay (PEOPLE: International Journal of Social Sciences, 2017)
Intertextuality refers to a "pre-text", which a text is already given. It often happens to a traveler that several second-hand texts, which arise from his cultural universe, furnish the materials of his travel narrative. Indeed, travel writing consists not only of seen things, but also of read things, of already learned texts, already written texts. Travel writing is the place of storage of second-hand knowledge, a pre-acquired knowledge about seen reality. The travel narrative often goes hand in hand with a heterogeneous text. Indeed, the narrator is in possession of a certain knowledge of the country visited which originates in a pre-trip: visiting museums, galleries, reading of other travel stories, tourist guides, History of the country visited before the traveler arrives there; Let us add to this list the humanist education that a Western traveler will use in front of the mythological sites, in front of Troy for example, and the fashion of the journey to the Orient in the nineteenth century which gave birth to several voyages and clichés, Or commonplaces, the smallest forms of second-hand knowledge often introduced into the text without quotation marks. The travel narrative largely draws its materials from other works or repeats images already known to the public. Here we do not intend to study all intertextual phenomena in the travel narrative, but rather to dwell on one of the processes of intertextuality: the stereotype. Stereotyped discourse does not take into account the reality of the object on which it bears, or of the original and personal subjectivity which expresses it. Only the conformity to an earlier model which is faithfully reproduced a model that is not in reality, fluctuating and unstable, but in a fixed rhetorical tradition. This double characteristic of the topos - belonging to rhetoric, a tendency to repetition - also shows its fundamental incompatibility with the realistic writing of the travel narrative, which calls for a completely different style: the effacement of rhetoric in favor of the observation of the real. Allegiance of the writing to all the modifications that can know the outside world. Our text of reference will be Theophile Gautier’s Constantinople. The elevation often assumed by Th. Gautier shows that he is not always a fervent supporter of description, and he has not set himself the task of restoring reality in its totality with minute accuracy. His mimetic discourse often uses a stereotyped discourse, a second-hand knowledge